Synthesis of Polyamidoxime Chelating Ligand from Polymer-Grafted Corn-Cob Cellulose for Metal Extraction - Lutfor, M. R.; Nik Rohani, Nik Mustapa; M. M., Yusoff (Wiley, 2014)
A conventional free-radical initiating process was used to prepare graft copolymers from acrylonitrile (AN) with corn-cob cellulose with ceric ammonium nitrate (CAN) as an initiator. The optimum grafting was achieved with corn-cob cellulose (anhydroglucose unit, AGU), mineral acid (H2SO4), CAN, and AN at concentrations of 0.133, 0.081, 0.0145, and 1.056 mol/L, respectively. Furthermore, the nitrile functional groups of the grafted copolymers were converted to amidoxime ligands with hydroxylamine under basic conditions of pH 11 with 4 h of stirring at 70C. The purified acrylic polymer-grafted cellulose and polyamidoxime ligand were characterized by Fourier transform infrared spectroscopy and field emission scanning electron microscopy analysis. The ligand showed an excellent copper binding capacity (4.14 mmol/g) with a faster rate of adsorption (average exchange rate =7 min), and it showed a good adsorption capacity for other metal ions as well. The metal-ion adsorption capacities of the ligand were pH-dependent in the following order: Cu2>Co2>Mn2>Cr3>Fe3>Zn2>Ni2. The metal-ion removal efficiency was very high; up to 99% was removed from the aqueous media at a low concentration. These new polymeric chelating ligands could be used to remove aforementioned toxic metal ions from industrial wastewater.